Plataforma virtual “novo professor”: da narratividade exitosa sobre o professor e sobre a aula. - Rezende, Bruna Oliveiro (Universidade Federal do Tocantins, 2022)
In this work, we focus on 05 videos available on the "Novo Professor" virtual platform, on YouTube, with the following general aim: problematize and analyze how the teacher and class are signified in such videos. Inscribed in the assumptions of the French Discourse Analysis of Pecheutian orientation, we conceive these videos as symbolic objects, which are fruits of a historicity. It is that they are born within the scope of the discursive practice of producing pedagogical videos having cyber circulation. The problematization we undertake in this work is limited to the fact that these videos put into circulation discursivities ready to use and consume about what is the teacher and the lesson. Depending on who comes in contact with the discursivities "prêt-à-porter", the complexity issue is superficialized in favor of what we are demonstrating of "successful narrativity about the teacher and about the classroom." Through discursive cuts (RD), selected from the phonetic transcriptions of the videos in focus, we proceeded to beet between transcription and interpretation of the clippings, in order to show how the adjectivation and adverbialization relations mean the teacher and the lesson. The discursive perspective anchors the perspective that this meaning does not arise out of nothing, on the contrary, it has an anchorage in and by historicity. The analyzes show that the teacher and the class are signified in the light of a technicist discursivitie, creating the illusion that it would be enough to follow the discursive procedures in the videos in order to have what they call a "class of excellence". Guided in a neoliberal discursivity, the meaning of the teacher and the class integrate the vision of education as a commodity to its consumer.